Il potenziamento cognitivo tra autodeterminazione e salute: tutele costituzionali tradizionali per possibilità scientifiche nuove (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The article addresses cognitive enhancement and its compatibility with the Italian constitutional system. It identifies self-determination and health protection, viewed in the light of the most recent interpretations, as the constitutional framework in which the right to enhancement could find its own space. However, in the same constitutional devices, as well as in the principle of equality, one can also identify the source of limitations to the exercise of such right. Finally, the article considers cognitive enhancement in the military field and genetic enhancement, which, together with other values of constitutional importance, could lead to different considerations regarding their compatibility with our legal system.
Keywords: Cognitive enhancement; self-determination; health protection; principle of equality; Code of medical ethics